How to do biography : a primer - Hamilton, Nigel (Harvard University Press, 2008)
Following his recent Biography: A Brief History (from Harvard), award-winning biographer and teacher Nigel Hamilton tackles the practicalities of doing biography in the first succinct primer to elucidate the tools of the biographer's craft.